Additive for anhydrous stemming and preparation method thereof
By preparing additives for water-free cannon mud containing components such as forsterilite and lene, the problems caused by water-free cannon mud in the prior art are solved, and high strength, stability and anti-oxidation are achieved in the existing technology. Improved performance and environmentally friendly and pollution-free.
Patent Information
- Application Number
- CN202411339588.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-27
AI Technical Summary
Existing water-announced cannon mud additives cause environmental pollution, making it difficult to promote sintering at lower temperatures, and the glass phase generated at high temperatures affects volume stability, reducing anti-oxidation and corrosion resistance.
20 to 30 wt% of 85 alumina clinker, 15 to 25 wt% of forsterite, 4 to 6 wt% of wt% of wt% of wt% of 95 silicon carbide, 5 to 7 wt% of 90 silicon carbide, 22 to 27 wt% of ferrosilicon nitride, 9 to 13 wt% coke powder, 6 to 8 wt% metal Si powder, 14 to 20 wt% white mud, and 2 to 4 wt% high temperature asphalt, 1 to 2 wt% carbon black, 15 ~18% by weight of the cannon sludge oil was mixed by mixing the water-annon sludge additives for 20 to 30 minutes.
It improves the mechanical strength, stability, oxidation and corrosion resistance of waterless cannon mud, reduces porosity, enhances sintering performance, and is environmentally friendly and pollution-free.
Smart Images

Figure BDA0005059308900000051 
Figure BDA0005059308900000091 
Figure BDA0005059308900000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of anhydrous taphole mud, and particularly relates to an additive for anhydrous taphole mud and a preparation method thereof. Background Art
[0002] With the development of metallurgical industry, blast furnaces are developing towards large-scale, durable and large slag discharge directions, which requires continuous improvement and optimization of raw materials and performance of cannon clay, an amorphous refractory material used in the taphole of blast furnaces. With continuous development, cannon clay is no longer just a single consumable refractory material, but has gradually become a functional refractory material with multiple functions such as protecting the taphole, reducing wear, and allowing molten iron to be discharged stably; cannon clay can be roughly divided into two categories in terms of composition: water cannon clay and anhydrous cannon clay. The difference lies in the binder. Water cannon clay is composed of alumina clinker, pyrophyllite and other aggregates, appropriately added with additives to improve construction performance and sintering performance, and is a refractory plastic made of binders such as cement; anhydrous cannon clay is made of high-alumina alumina clinker, white mud, carbon black, silicon carbide, asphalt, coke powder and other raw materials as the main raw materials, and the raw materials are bonded by tar or phenolic resin. The raw material particle level of anhydrous cannon clay The influence of the mixing composition on the construction and sintering performance is generally consistent with that of water-containing cannon mud. Increasing the proportion of coarse particles in the composition can reduce the extrusion pressure of the cannon mud, reduce the porosity after heating, improve plasticity, and improve workability. However, when the coarse particles reach a certain proportion, the porosity increases and the sintering property deteriorates. The introduction of suitable additives is one of the effective ways to further improve the performance of anhydrous cannon mud. However, excessive asphalt in the additives will seriously pollute the environment. It is difficult to promote the sintering of cannon mud at low temperatures, and the cannon mud cannot obtain high strength. At high temperatures, more glass phases will be produced in the cannon mud, affecting the volume stability of the cannon mud. Therefore, the antioxidant properties of the cannon mud cannot be effectively improved, but the erosion resistance of the cannon mud is significantly reduced. Therefore, it is very necessary to provide an environmentally friendly and pollution-free anhydrous cannon mud additive and a preparation method thereof that effectively improves strength and stability, and enhances antioxidant and erosion resistance. Summary of the invention
[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and to provide an environmentally friendly, pollution-free, effectively improving strength and stability, and enhancing antioxidant and anti-corrosion properties of an anhydrous taphole mud additive and a preparation method thereof.
[0004] The object of the present invention is achieved in this way: the preparation method of anhydrous cannon clay additive, first with 20-30wt% of 85 alumina clinker, 15-25wt% of forsterite, 4-6wt% of pyrophyllite, 6-8wt% of 95 silicon carbide, 5-7wt% of 90 silicon carbide, 22-27wt% of ferrosilicon nitride, 9-13wt% of coke powder, 6-8wt% of metal Si powder, 14-20wt% of white mud as raw materials, then add 2-4wt% of high-temperature asphalt of the raw materials, 1-2wt% of carbon black, 15-18wt% of cannon clay oil, mix in a mixer for 20-30 minutes, and obtain anhydrous cannon clay additive.
[0005] The particle size of the 85 alumina clinker is 10-19wt% in the range of 3-1mm, 7-13wt% in the range of 1-0mm, and 3-5wt% in the range of ≤0.074mm.
[0006] The forsterite particle size of 3-1 mm accounts for 9-19 wt %, 1-0 mm accounts for 6-13 wt %, and ≤0.074 mm accounts for 2-5 wt %.
[0007] The forsterite can be replaced by 11-24wt% of fused magnesia, wherein the particle size of the fused magnesia is 9-19wt% for 3-1mm, 6-13wt% for 1-0mm, and 2-5wt% for ≤0.074mm.
[0008] The forsterite can be replaced by 10-20wt% of quartz sand, wherein the quartz sand with a particle size of 3-1mm accounts for 9-19wt%, the quartz sand with a particle size of 1-0mm accounts for 6-13wt%, and the quartz sand with a particle size of ≤0.074mm accounts for 2-5wt%.
[0009] The metal Si powder can be replaced by 5-7 wt% of aluminum oxide powder.
[0010] The metal Si powder can be replaced by 7-8 wt % of sodium bentonite.
[0011] The metal Si powder can be replaced by 5-8wt% silicon-carbon micropowder with a particle size of 3000 mesh.
[0012] The particle size of the pyrophyllite is 3-1mm; the particle size of the 95 silicon carbide is 1-0mm; the particle size of the coke powder is 1-0mm90; the particle size of the silicon carbide is ≤0.074mm; and the particle size of the ferrosilicon nitride is ≤0.074mm.
[0013] The additive for anhydrous cannon clay is an additive for anhydrous cannon clay prepared according to the preparation method of the additive for anhydrous cannon clay described above.
[0014] The invention has the following beneficial effects: the invention provides an additive for anhydrous cannon mud and a preparation method thereof. In use, the invention adopts forsterite as an aggregate to avoid volume expansion caused by secondary mullite, and the iron dissolved in forsterite can promote the sintering of cannon mud. The cannon mud with forsterite as an aggregate has a small expansion coefficient, high mechanical strength, and plasticity that meets the requirements of construction performance. The invention adopts 50% fused magnesia as an aggregate to improve the mechanical strength of cannon mud at room temperature. Alumina and fused magnesia generate a large amount of magnesia-alumina spinel under high temperature, and the magnesia-alumina spinel has a large volume density. The structure is uniform, the quality is stable, the corrosion resistance is strong, and the flexural strength and compressive strength of the cannon mud are increased; the present invention adopts quartz sand to completely replace the alumina clinker in the cannon mud, which can improve the mechanical properties of the cannon mud at room temperature, increase the bulk density and reduce the apparent porosity; the present invention adopts metal silicon powder as an additive and adds it to the cannon mud to improve the flexural strength, compressive strength and bulk density of the cannon mud, and reduce the apparent porosity of the cannon mud; the present invention adopts sodium-based bentonite to improve the plasticity of the cannon mud; the present invention has the advantages of being environmentally friendly and pollution-free, effectively improving strength and stability, and enhancing antioxidant and corrosion resistance. DETAILED DESCRIPTION
[0015] The sample preparation of the present invention is specifically as follows: ① batching and mixing: accurately weigh the raw materials and binders according to the formula of the present invention and mix them evenly according to the standard; ② molding: prepare a 40mm×40mm×160mm mold, clean the surface and evenly apply lubricating oil, weigh 650g of the mixed material and put it into the mold, place the mold at the center of the pressure testing machine operating table, press it with a pressure of 80kN (125MPa), and maintain the pressure for 30s; ③ demolding: remove the bottom of the pressed mold, place it on the operating table in reverse, install the demolding mold and manually demold it; ④ firing: the pressed sample is placed at room temperature for 48 hours, and then buried in carbon for heat treatment at 800℃, 1200℃, and 1450℃ according to the designed firing curve. After keeping warm for 3h, stop heating and cool it naturally to room temperature with the furnace to take out the sample.
[0016] The specific performance tests are as follows: using a YAW-100 microcomputer-controlled pressure testing machine to test the room-temperature flexural strength of the fired cannon mud; using a WAW-1000 microcomputer-controlled electro-hydraulic servo universal testing machine to test the room-temperature compressive strength of the fired cannon mud; testing the volume density and apparent porosity of the fired cannon mud according to GB / T2997-2000; testing the linear change rate of the cannon mud sample after 1450°C calcination according to GB / T5988-2007; using a GDP-500 detector to test the Maxwell value of the sample; using an X'pert-Powder X-ray diffractometer (Cu target, tube voltage: 40kV, tube current: 40mA, step size 0.013°, scanning range 10°-90°) to test the phase composition of the fired cannon mud; and using a ∑IGMAHD field emission scanning electron microscope to observe the microstructure of the cannon mud.
[0017] The present invention is further described below.
[0018] Example 1
[0019] The preparation method of an anhydrous cannon clay additive comprises the following steps: firstly using 20wt% of 85 alumina clinker, 15wt% of forsterite, 4wt% of pyrophyllite, 6wt% of 95 silicon carbide, 5wt% of 90 silicon carbide, 22wt% of ferrosilicon nitride, 9wt% of coke powder, 6wt% of metal Si powder and 14wt% of white mud as raw materials, and then adding 2wt% of high-temperature asphalt, 1wt% of carbon black and 15wt% of cannon clay oil to the raw materials, and mixing the mixture in a mixer for 20 minutes to obtain an anhydrous cannon clay additive.
[0020] The particle size of the 85 alumina clinker is 3-1mm, accounting for 10wt%, 1-0mm, accounting for 7wt%, and ≤0.074mm, accounting for 3wt%.
[0021] The forsterite particle size of 3-1 mm accounts for 9 wt %, 1-0 mm accounts for 6 wt %, and ≤0.074 mm accounts for 2 wt %.
[0022] In this embodiment, the influence of forsterite on the performance of cannon mud: forsterite is a weakly alkaline refractory material with stable chemical properties, small thermal expansion coefficient and high thermal conductivity; forsterite, as a calcium-free and rich magnesium oxide source, can improve the desulfurization and alkali removal capacity of slag and reduce the harmful circulation of alkali metals in the blast furnace; the present invention uses forsterite to replace the high-alumina bauxite clinker in the anhydrous cannon mud, and analyzes the mechanical properties and usage performance of forsterite on the cannon mud. The specific experimental formula is shown in Table 1; the test sample in which all the aggregates are high-alumina bauxite is recorded as F, the sample in which all the aggregates are forsterite is recorded as M1, and the sample in which the aggregates are 50% high-alumina bauxite and 50% forsterite is recorded as M2.
[0023] Table 1 Experimental formula / wt%
[0024]
[0025] ① Mechanical properties at room temperature: After being calcined at 1200℃, the flexural strength of samples F and M2 reached the peak value, while the curve trend of M1 was the opposite, and its flexural strength first decreased and then increased; after heat treatment at 800℃, the flexural strength of samples F and M1 was 2MPa, and the flexural strength of M2 was 1MPa, which was due to the volatilization of organic matter such as tar and asphalt at this temperature; at 1200℃, Si0 2It reacts with the carbonaceous materials in the cannon mud to generate silicon carbide, which makes the matrix self-bonded, so the flexural strength of samples F and M2 is improved; while forsterite is chemically stable below 1200℃ and it is difficult to react with the substances in the components, so the flexural strength of sample M1 is lower than that of samples F and M2; after being calcined at 1450℃, the volume of alumina in samples F and M2 expands due to secondary mullite formation, which reduces the density of the samples and thus leads to lower flexural strength, while forsterite in M1 also expands in volume above 1450℃, but its expansion coefficient is smaller than that of sample F, and the iron dissolved in the stone forms a liquid phase to promote the sintering of sample M1 and promote the combination of silicon nitride and carbon to strengthen the matrix, thereby improving its flexural strength;
[0026] After calcining at 800°C, the compressive strength of sample F is 6MPa, and the compressive strength of samples M1 and M2 is 5MPa; after calcining at 1200°C, the compressive strength of sample M1 decreases to 2MPa; when the calcination temperature is increased to 1450°C, the compressive strength of sample F is 7MPa, and the compressive strength of sample M2 is 11MPa, among which the compressive strength of sample M1 is the highest at 13MPa; with the increase of calcination temperature, the iron dissolved in forsterite begins to melt, acting as a liquid phase, promoting the sintering of the internal material of the cannon mud, shrinking the volume, reducing the porosity, and increasing the compressive strength.
[0027] ② Bulk density and apparent porosity: After calcination at 800℃, the bulk densities of samples F, M1, and M2 are 1.989 g / cm 3 , 1.946g / cm 3 , 1.967g / cm 3 After calcination at 1200℃, a large amount of volatiles such as tar and asphalt were discharged, making the sample loose, and the volume density of sample M1 dropped to 1.926g / cm 3 , the volume density of sample M2 dropped to 1.946 g / cm 3 ; The Si0 contained in the alumina clinker of sample F 2 Combined with carbon materials in the cannon mud to form SiC, its density is improved, thereby increasing the bulk density; after calcination at 1450℃, the iron dissolved in the forsterite begins to melt, acting as a liquid phase, promoting the sintering of the material inside the cannon mud, volume shrinkage, and increased bulk density. The bulk density of sample M1 reached 1.940g / cm 3 ; In samples F and M2, alumina undergoes mullitization reaction to generate mullite. As the calcination temperature increases, mullite begins to grow, expands in volume, and decreases in volume density;
[0028] When the roasting temperature is 800℃ and 1200℃, the apparent porosity of the three cannon clay samples remains at around 29-30%; when the roasting temperature is 1450℃, the apparent porosity of sample M1 drops to 21.3%; the apparent porosity depends on the volatilization degree of the binder after the temperature rises and the sintering strength inside the cannon clay. When the roasting temperature is 800℃, the sample is in a stage where tar and asphalt burn to produce a large amount of volatiles and gases, but because the coke powder in the raw material has a porous structure that allows volatiles and gases to be quickly discharged, its apparent porosity does not change much; when the roasting temperature rises to 1450℃, the iron dissolved in forsterite begins to liquefy to produce a liquid phase, which improves the sintering strength, increases the bulk density, and reduces the porosity; with the increase in roasting temperature and the increase in forsterite content, more liquid phases are produced, the sintering performance is enhanced, the porosity is reduced, and the porosity of M1 is only 21.3%.
[0029] ③ Linear change rate: With the increase of roasting temperature, the linear change rate of samples M1 and M2 shows a decreasing trend. This is because forsterite produces a liquid phase under high temperature, which promotes the sintering of the sample, shrinks the volume, and reduces the linear change rate. With the increase of forsterite content, the sintering strength is enhanced. Sample M1 has the highest forsterite content, the largest volume shrinkage, and the smallest linear change rate. With the increase of roasting temperature, sample F undergoes mullite reaction, expands the volume, and increases the linear change rate.
[0030] ④ Maxwell value: The Maxwell value of sample F is 0.546MPa, and those of samples M1 and M2 are 0.591MPa and 0.553MPa respectively, all of which meet the use requirements of cannon clay. With the increase of forsterite content, the Maxwell value of cannon clay increases, but the increase is very small. The amount of forsterite added is not the main factor affecting the change of the Maxwell value of cannon clay.
[0031] ⑤XRD diffraction analysis: After samples F, M1 and M2 were calcined at 1450℃, the mineral phase of sample F was mainly silicon nitride, corundum, mullite, wollastonite and cristobalite; the mineral phase of sample M1 was mainly silicon nitride and forsterite; the main mineral phases of sample M2 were silicon nitride, mullite and forsterite; both samples F and M2 had mullite, and as the temperature increased, the mullite grew, which reduced the volume density of the cannon mud.
[0032] ⑥Scanning electron microscope analysis: After being roasted at 1450℃, sample F has many dense pores with large pore diameter, deep holes, different sizes and irregular distribution. When tapping iron, molten iron enters the pores and destroys the tapping port. After being roasted at 1450℃, samples M1 and M2 have a large amount of iron around the forsterite particles, forming a liquid phase under the action of high temperature, acting as a sintering aid, and wrapping around the forsterite after cooling. With the increase of forsterite addition, the pores are significantly reduced, the holes become shallower, and most of the pores are filled. Forsterite can reduce the porosity of cannon mud.
[0033] The particle size of the pyrophyllite is 3-1mm; the particle size of the 95 silicon carbide is 1-0mm; the particle size of the coke powder is 1-0mm90; the particle size of the silicon carbide is ≤0.074mm; and the particle size of the ferrosilicon nitride is ≤0.074mm.
[0034] The invention discloses an additive for anhydrous cannon mud and a preparation method thereof. In use, the invention adopts forsterite as an aggregate to avoid volume expansion caused by secondary mullite, and the iron dissolved in forsterite can promote the sintering of cannon mud. The cannon mud with forsterite as an aggregate has a small expansion coefficient, high mechanical strength, and plasticity that meets the requirements of construction performance. After being calcined at 1450°C, the cannon mud has a flexural strength and a compressive strength of 3MPa and 13MPa respectively, and a volume density of 1.940g / cm 3 , the apparent porosity is 21.4%; the present invention uses 50% fused magnesia sand as aggregate to improve the mechanical strength of cannon mud at room temperature. Alumina and fused magnesia sand generate a large amount of magnesia-alumina spinel under high temperature. The magnesia-alumina spinel has a large volume density, uniform structure, stable quality, strong corrosion resistance, and increases the flexural strength and compressive strength of cannon mud; the present invention uses quartz sand to completely replace the alumina clinker in the cannon mud to improve the mechanical properties of the cannon mud at room temperature, increase the volume density and reduce the apparent porosity; the present invention uses metal silicon powder as an additive to add to the cannon mud to improve the flexural strength, compressive strength and volume density of the cannon mud, and reduce the apparent porosity of the cannon mud. The metal silicon powder combines with the carbon material in the cannon mud at high temperature to generate silicon carbide. After being roasted at 1450°C, the flexural strength is increased to 10.45MPa, the compressive strength is increased to 13MPa, and the volume density is increased to 2.105g / cm 3 , the apparent porosity is reduced to 25.2%; the sodium-based bentonite used in the present invention can improve the plasticity of the taphole mud; the present invention has the advantages of being environmentally friendly and pollution-free, effectively improving strength and stability, and enhancing antioxidant and anti-corrosion properties.
[0035] Example 2
[0036] An additive for anhydrous cannon clay and a preparation method thereof. The preparation method of the additive for anhydrous cannon clay comprises the following steps: firstly using 25wt% of 85 alumina clinker, 20wt% of fused magnesia, 5wt% of pyrophyllite, 7wt% of 95 silicon carbide, 6wt% of 90 silicon carbide, 24wt% of ferrosilicon nitride, 11wt% of coke powder, 6wt% of alumina powder and 17wt% of white mud as raw materials, and then adding 3wt% of high-temperature asphalt, 1.5wt% of carbon black and 17.5wt% of cannon clay oil to the raw materials, and mixing the mixture in a mixer for 25 minutes to obtain the additive for anhydrous cannon clay.
[0037] The particle size of the 85 alumina clinker is 3-1mm, accounting for 14.5wt%, 1-0mm, accounting for 10wt%, and ≤0.074mm, accounting for 4wt%.
[0038] The forsterite can be replaced by 11-24wt% of fused magnesia, wherein the fused magnesia has a particle size of 3-1mm at 14wt%, 1-0mm at 9.5wt%, and <0.074mm at 3.5wt%.
[0039] In this embodiment, the influence of fused magnesia on the performance of taphole mud: fused magnesia is a high-temperature resistant raw material with excellent performance, good corrosion resistance, stable chemical properties, dense structure and high refractoriness. The raw material purity of fused magnesia is extremely high and the impurity content is low, which can reduce the influence of impurities on anhydrous taphole mud; the present invention selects fused magnesia as an additive for preparing anhydrous taphole mud, and the specific experimental scheme is shown in Table 2; the test is performed by recording the sample in which all aggregates are high-alumina bauxite as F, the sample in which all aggregates are fused magnesia as D1, and the sample in which the aggregates are 50% high-alumina bauxite and 50% fused magnesia as D2.
[0040] Table 2 Experimental formula / wt%
[0041]
[0042]
[0043] ① Mechanical properties at room temperature: Samples F, D1, and D2 were calcined at 800℃, 1200℃, and 1450℃, respectively. After calcination at 800℃, the flexural strength of sample F was 2MPa, and the flexural strength of samples D1 and D2 was 1MPa. This is due to the volatilization of organic matter such as tar and asphalt at this temperature; after calcination at 1200℃, the flexural strength of sample F was 4MPa, the flexural strength of sample D1 was 3MPa, and the flexural strength of sample D2 was 3.5MPa. The SiO in alumina 2 It reacts with the carbon materials in the cannon mud to generate silicon carbide, which causes the matrix to self-bond, so the flexural strength of samples F and D2 is improved; after calcination at 1450℃, the flexural strength of samples F and D1 is 1MPa, and the flexural strength of sample D2 is 2MPa. The alumina and fused magnesia in sample D2 generate a large amount of magnesia-alumina spinel under high temperature. The magnesia-alumina spinel has a large volume density, uniform structure, stable quality, and strong corrosion resistance, which increases the flexural strength and compressive strength of the cannon mud; fused magnesia has stable chemical properties, high raw material purity, and dense structure. It does not react with other substances after calcination at 800℃, 1200℃, and 1450℃, and its compressive strength is only 2MPa, 3MPa, and 3MPa.
[0044] ② Bulk density and apparent porosity: Samples F, D1, and D2 were calcined at 800°C, 1200°C, and 1450°C, respectively. When the calcination temperature rose to 1200°C, the bulk density of samples F, D1, and D2 was 2.025 g / cm 3 , 2.001g / cm 3, 2.018g / cm 3 The apparent porosity is 27.8%, 29.9%, and 28.7%, and the Si0 2 Combined with carbon materials in taphole mud to form SiC, the density is improved, and then the bulk density is increased and the apparent porosity is reduced; after calcination at 1450℃, the bulk densities of samples F, D1 and D2 are 1.904g / cm 3 , 1.788g / cm 3 , 1.845g / cm 3 With the increase of fused magnesia content, the bulk density of taphole clay gradually decreases and the apparent porosity gradually increases. The main phase of fused magnesia, periclase, has a high thermal expansion coefficient. When the temperature rises, the volume expands greatly, the bulk density decreases, and the apparent porosity increases.
[0045] ③ Linear change rate: Samples F, D1, and D2 were calcined at 800℃, 1200℃, and 1450℃, respectively. As the content of fused magnesia gradually increased, the linear change rate increased significantly. As the calcination temperature increased, the linear change rates of samples F, D1, and D2 also increased. The highest linear change rate of sample F did not exceed 1.25%, the highest linear change rate of sample D1 had reached 2.8%, and the highest linear change rate of sample D2 also exceeded 2%. The thermal expansion coefficient of fused magnesia is much higher than that of alumina. The more fused magnesia is added, the greater the volume expansion and the higher the linear change rate. When adding fused magnesia, be sure to control the appropriate amount.
[0046] ④ Maxwell value: The Maxwell values of samples F, D1 and D2 are 0.546MPa, 0.524MPa and 0.534MPa respectively. With the increase of fused magnesia content, the Maxwell value decreases all the time, but the decrease is very small. The amount of fused magnesia added is not the main factor affecting the change of Maxwell value of cannon mud.
[0047] ⑤XRD diffraction analysis: Samples F, D1 and D2 were calcined at 1450℃, and the mineral phase of sample F was mainly silicon nitride, corundum, mullite, wollastonite and quartz; the main mineral phases of sample D1 were periclase, silicon nitride, forsterite and silicon carbide; the main mineral phases of sample D2 were silicon carbide, periclase, magnesia-alumina spinel and silicon carbide; the presence of magnesia-alumina spinel in sample D2 improved the flexural strength and compressive strength of the cannon mud after calcination at 1450℃; periclase was present in both samples D1 and D2, and with the increase of heat treatment temperature, periclase expanded, reducing the volume density of the cannon mud and increasing the porosity.
[0048] ⑥Scanning electron microscope analysis: After samples D1 and D2 were calcined at 1450℃, a large number of microcracks appeared on the surface of sample D1. The thermal expansion coefficient of periclase was too high, resulting in serious bulging of most areas on the surface of the cannon mud, decreased density, reduced bulk density, and increased apparent porosity. The surface of the periclase in sample D2 was slightly neater than that in D1. Alumina and fused magnesia in sample D2 generated magnesia-alumina spinel, which improved the flexural strength and compressive strength of the cannon mud after calcination at 1450℃.
[0049] The metal Si powder can be replaced by 5-7 wt% of aluminum oxide powder.
[0050] The particle size of the pyrophyllite is 3-1mm; the particle size of the 95 silicon carbide is 1-0mm; the particle size of the coke powder is 1-0mm90; the particle size of the silicon carbide is ≤0.074mm; and the particle size of the ferrosilicon nitride is ≤0.074mm.
[0051] The invention relates to an additive for anhydrous cannon mud and a preparation method thereof. In use, the invention adopts forsterite as an aggregate to avoid volume expansion caused by secondary mullite, and the iron dissolved in forsterite can promote the sintering of cannon mud. The cannon mud with forsterite as an aggregate has a small expansion coefficient, high mechanical strength, and plasticity that meets the requirements of construction performance. The invention adopts 50% fused magnesia as an aggregate to improve the mechanical strength of cannon mud at room temperature. Alumina and fused magnesia generate a large amount of magnesia-aluminum spinel under high temperature. The magnesia-aluminum spinel has a large volume density, uniform structure, stable quality, strong corrosion resistance, and increases the cannon mud. The flexural strength and compressive strength of the cannon mud are 2MPa and 8MPa respectively after being calcined at 1450℃; the present invention adopts quartz sand to completely replace the alumina clinker in the cannon mud, which can improve the mechanical properties of the cannon mud at room temperature, increase the bulk density and reduce the apparent porosity; the present invention adopts metal silicon powder as an additive and adds it to the cannon mud to improve the flexural strength, compressive strength and bulk density of the cannon mud, and reduce the apparent porosity of the cannon mud; the present invention adopts sodium-based bentonite to improve the plasticity of the cannon mud; the present invention has the advantages of being environmentally friendly and pollution-free, effectively improving strength and stability, and enhancing antioxidant and anti-corrosion properties.
[0052] Example 3
[0053] An additive for anhydrous cannon clay and a preparation method thereof. The preparation method of the additive for anhydrous cannon clay comprises the following steps: firstly using 30wt% of 85 alumina clinker, 20wt% of quartz sand, 6wt% of pyrophyllite, 8wt% of 95 silicon carbide, 7wt% of 90 silicon carbide, 27wt% of ferrosilicon nitride, 13wt% of coke powder, 8wt% of sodium bentonite, 8wt% of silicon-carbon micropowder, and 20wt% of white mud as raw materials, and then adding 4wt% of high-temperature asphalt, 2wt% of carbon black, and 18wt% of cannon clay oil to the raw materials, and mixing the mixture in a mixer for 30 minutes to obtain the additive for anhydrous cannon clay.
[0054] The particle size of the 85 alumina clinker is 3-1mm, accounting for 19wt%, 1-0mm, accounting for 13wt%, and ≤0.074mm, accounting for 5wt%.
[0055] The forsterite can be replaced by 10-20wt% of quartz sand, wherein the quartz sand with a particle size of 3-1mm is 19wt%, 1-0mm is 13wt%, and <0.074mm is 5wt%.
[0056] In this embodiment, the effect of quartz sand on the performance of taphole mud: quartz sand is a hard, wear-resistant, chemically stable silicate mineral, the main mineral component of which is Si0 2 The present invention uses quartz sand to replace high-alumina bauxite in anhydrous cannon mud, and measures its compressive strength, flexural strength, bulk density, apparent porosity and 60°C Marshal value after calcination at 800°C, 1200°C and 1450°C respectively; the phase composition and microstructure of the anhydrous cannon mud are characterized by X-ray diffraction and scanning electron microscopy, and the specific experimental formula is shown in Table 3; the sample prepared with all high-alumina bauxite as aggregate is marked as F, the sample prepared with all quartz sand as aggregate is marked as S1, and the sample prepared with 50% high-alumina bauxite and 50% quartz sand as aggregate is marked as S2.
[0057] Table 3 Experimental formula / wt%
[0058]
[0059] ① Mechanical properties at room temperature: The maximum flexural strength of samples F and S2 fired at 1200℃ is 4MPa and 3.5MPa respectively. When the calcination temperature rises to 1450℃, the flexural strength of samples F and S2 drops to 1MPa and 2MPa respectively. After calcination at 1450℃, the flexural strength of sample S2 is slightly greater than that of sample F. Due to the secondary mullite action of alumina, the sample structure becomes loose and the flexural strength decreases. As the calcination temperature rises, the flexural strength of sample S1 increases. The large amount of carbon materials contained in the taphole mud react with Si0 2 Reduction reaction occurs SiO 2 +C=Si+CO, Si+C=SiC, a part of silicon carbide is generated, which improves the flexural strength of the taphole mud. When the roasting temperature is 1450℃, the flexural strength reaches 3MPa;
[0060] The compressive strength of sample S1 after calcination at 800℃, 1200℃, and 1450℃ is 7MPa, 7MPa, and 8MPa respectively. The quartz sand particles are hard and the structure is dense when extruded, so the compressive strength of sample S1 is large. As the temperature rises, the large amount of carbon materials contained in the taphole mud react with Si0 2 Reduction reaction occurs SiO2 +C=Si+CO, Si+C=SiC, generating a part of silicon carbide, which improves the compressive strength of the cannon mud.
[0061] ② Bulk density and apparent porosity: The bulk density and apparent porosity of samples F, S1, and S2 at calcination temperatures of 800℃, 1200℃, and 1450℃, respectively. The bulk density of sample S2 is lower than that of sample F. In sample S2, quartz sand and alumina participate in the reaction together. When the heat treatment temperature is below 1200℃, the quartz sand is chemically stable. When the calcination temperature reaches 1450℃, the alumina in the component undergoes a mullite reaction, and the volume expands during the sintering process, the bulk density decreases, and the porosity increases. When the calcination temperature of sample S1 increases from 1200℃ to 1450℃, a series of reduction reactions occur, SiO 2 +C=Si+CO, Si+C=SiC, generating a part of silicon carbide and elemental Si, which promotes the sintering of taphole mud, increases the bulk density and reduces the porosity; when the heat treatment temperature is 1450℃, the bulk density of sample S1 reaches 1.986g / cm 3 , the porosity dropped to 27%.
[0062] ③ Line change rate: The line change is generally controlled between 0.8-1.6. A value greater than 1 indicates sample expansion, and a value less than 1 indicates sample contraction. The ideal state of taphole clay is slight expansion, that is, when the calcination temperature is 1450℃, the line change rate should not exceed 1.6. With the increase of calcination temperature, the line change rates of the three samples gradually increase. When the calcination temperature of samples F and S1 increases from 800℃ to 1450℃, the volumes of the samples shrink first and then slightly expand. The volume of sample S2 has been expanding, and its line change rate is much greater than that of the other two groups. The Si0 2 A1 in bauxite 2 0 3 The reaction generates a large amount of mullite. As the temperature rises, the mullite grains grow, causing the volume of sample S2 to expand too dramatically, affecting the performance of the taphole mud.
[0063] ④ Maxwell value: The Maxwell value of sample F is 0.501MPa, the Maxwell value of sample S1 is 0.543MPa, and the Maxwell value of sample S2 is 0.518MPa. The Maxwell values of the three samples are all above 0.5, and with the increase of quartz sand content, the decrease is very small. The amount of quartz sand added is not the main factor affecting the change of Maxwell value of cannon mud.
[0064] ⑤XRD diffraction analysis: After different samples were calcined at 1450℃, the main crystal phase of sample F was mainly silicon nitride and silicon carbide, accompanied by the formation of a new phase of mullite. The mullites were interwoven to form a network structure to compensate for the volume shrinkage of the binder after carbonization, thereby increasing the volume density of the cannon mud and reducing the apparent porosity.
[0065] ⑥ Scanning electron microscope analysis: The bonding surface of quartz sand and alumina in group S2 has a large number of pores due to the volatilization of volatiles and the formation of mullite, which reduces the volume density of the cannon mud and increases the apparent porosity; the quartz sand in group S1 sample has hard quartz sand particles and a dense structure when extruded.
[0066] The particle size of the pyrophyllite is 3-1mm; the particle size of the 95 silicon carbide is 1-0mm; the particle size of the coke powder is 1-0mm90; the particle size of the silicon carbide is ≤0.074mm; and the particle size of the ferrosilicon nitride is ≤0.074mm.
[0067] The metal Si powder can be replaced by 7-8 wt % of sodium bentonite.
[0068] The invention relates to an additive for anhydrous cannon mud and a preparation method thereof. In use, the invention adopts forsterite as an aggregate to avoid volume expansion caused by secondary mullite, and the iron dissolved in forsterite can promote the sintering of cannon mud. The cannon mud with forsterite as an aggregate has a small expansion coefficient, high mechanical strength, and plasticity that meets the requirements of construction performance. The invention adopts 50% fused magnesia sand as an aggregate to improve the mechanical strength of cannon mud at room temperature. Alumina and fused magnesia sand generate a large amount of magnesia-alumina spinel under high temperature. The magnesia-alumina spinel has a large volume density, a uniform structure, stable quality, strong corrosion resistance, and increases the flexural strength and compressive strength of cannon mud. The invention adopts quartz sand to completely replace the alumina clinker in the cannon mud to improve the mechanical properties of the cannon mud at room temperature, increase the volume density and reduce the apparent porosity, and the Si0 2 With the large amount of carbon materials contained in the taphole mud, SiO2 undergoes a reduction reaction at high temperature. 2 +C=Si+CO, Si+C=SiC, generating a part of silicon carbide; when the calcination temperature is 1450℃, the flexural strength reaches 3MPa, the compressive strength reaches 8MPa, and the volume density reaches 1.986g / cm 3 , the porosity is reduced to 27%; the present invention adopts metal silicon powder as an additive and adds it to the cannon mud to improve the flexural strength, compressive strength, and bulk density of the cannon mud, and reduce the apparent porosity of the cannon mud; the present invention adopts sodium-based bentonite to improve the plasticity of the cannon mud; the present invention has the advantages of being environmentally friendly and pollution-free, effectively improving strength and stability, and enhancing antioxidant and anti-corrosion properties.
[0069] Example 4
[0070] An additive for anhydrous cannon clay and a preparation method thereof. The preparation method of the additive for anhydrous cannon clay comprises the following steps: firstly using 30wt% of 85 alumina clinker, 25wt% of forsterite, 24wt% of fused magnesia, 6wt% of pyrophyllite, 8wt% of 95 silicon carbide, 7wt% of 90 silicon carbide, 27wt% of ferrosilicon nitride, 13wt% of coke powder, 8wt% of silicon-carbon micropowder, and 20wt% of white mud as raw materials, and then adding 4wt% of high-temperature asphalt, 2wt% of carbon black, and 18wt% of cannon clay oil to the raw materials, and mixing the mixture in a mixer for 30 minutes to obtain the additive for anhydrous cannon clay.
[0071] The particle size of the 85 alumina clinker is 3-1mm, accounting for 19wt%, 1-0mm, accounting for 13wt%, and ≤0.074mm, accounting for 5wt%.
[0072] The quartz sand has a particle size of 3-1 mm accounting for 19 wt %, 1-0 mm accounting for 13 wt %, and <0.074 mm accounting for 5 wt %.
[0073] The particle size of the pyrophyllite is 3-1mm; the particle size of the 95 silicon carbide is 1-0mm; the particle size of the coke powder is 1-0mm90; the particle size of the silicon carbide is ≤0.074mm; and the particle size of the ferrosilicon nitride is ≤0.074mm.
[0074] The metal Si powder can be replaced by 8wt% silicon-carbon micropowder with a particle size of 3000 meshes.
[0075] In this embodiment, the composition of silicon carbon powder is shown in Table 4.
[0076] Table 4 Composition of silicon carbon powder
[0077] name Si / % SiC / % <![CDATA[SiO 2 / %]]> <![CDATA[Fe、Fe 2 THE 3 / %]]> granularity Silicon Carbon Powder >30 >40 <25 <5 3000
[0078] Advantages: 1. Small amount of addition, the addition amount is 5%-8%, depending on the on-site production; 2. High cost performance, when the same use requirements are met, the taphole mud can be reduced by 100-200 yuan per ton; 3. Fine particle size, 3000 mesh, uniform mixing; 4. Few harmful impurities, Si, SiC effective components reach more than 70%, Si0 2 Micropowder can improve the plasticity of cannon clay.
[0079] The invention relates to an additive for anhydrous cannon mud and a preparation method thereof. In use, the invention adopts forsterite as an aggregate to avoid volume expansion caused by secondary mullite, and the iron dissolved in forsterite can promote the sintering of cannon mud. The cannon mud with forsterite as an aggregate has a small expansion coefficient, high mechanical strength, and plasticity that meets the requirements of construction performance. The invention adopts 50% fused magnesia as an aggregate to improve the mechanical strength of cannon mud at room temperature. Alumina and fused magnesia generate a large amount of magnesia-aluminum spinel under high temperature, and the magnesia-aluminum spinel has a large volume density and a uniform structure. , stable quality, strong anti-erosion ability, and increased the flexural strength and compressive strength of cannon mud; the present invention uses quartz sand to completely replace the alumina clinker in the cannon mud, which can improve the mechanical properties of the cannon mud at room temperature, increase the bulk density and reduce the apparent porosity; the present invention uses metal silicon powder as an additive to add to the cannon mud to improve the flexural strength, compressive strength, and bulk density of the cannon mud, and reduce the apparent porosity of the cannon mud; the present invention uses sodium-based bentonite to improve the plasticity of the cannon mud; the present invention has the advantages of environmental protection and pollution-free, effectively improving strength and stability, and enhancing antioxidant and anti-erosion properties.
[0080] Further description of the present invention
[0081] In this embodiment, the influence of metallic silicon powder, sodium-based bentonite and alumina powder on the performance of cannon mud: metallic silicon powder, also known as industrial silicon powder, reacts with carbon at high temperature to form silicon carbide to improve the high temperature resistance, damage resistance and oxidation resistance of cannon mud; sodium-based bentonite has micro-expansion, which can resist the adverse effects of sintering shrinkage of cannon mud. Sodium-based bentonite has good thermal stability, high plasticity and strong adhesion; alumina powder has the characteristics of high purity, high density and good sintering performance; these three materials themselves have excellent properties of anti-erosion and anti-scouring. The present invention analyzes the influence of three fine powders on the performance of cannon mud. The specific experimental scheme is shown in Table 5; sample Si represents cannon mud with the addition of metallic silicon powder, sample Na represents cannon mud with the addition of sodium-based bentonite, and sample Al represents cannon mud with the addition of alumina powder.
[0082] Table 5 Experimental formula / wt%
[0083]
[0084] ① Mechanical properties at room temperature: After being calcined at 800℃, the flexural strengths of sample Si, sample Na, and sample A1 were 1.9MPa, 1.9MPa, and 1.7MPa, respectively. After being calcined at 800℃, only tar and asphalt reacted in the cannon mud, and the flexural strength of the cannon mud with different fine powders did not change much; when the cannon mud was calcined at 1200℃, the flexural strength of sample Si reached 6.3MPa, the flexural strength of sample Na was 2.8MPa, and the flexural strength of sample A1 was 2.4MPa, which were significantly higher than the flexural strengths of sample Na and sample A1; after the sample was calcined at 1450℃, the flexural strength of sample Si reached 10.4MPa. Under the action of high temperature, the metal silicon powder reacted with the carbon material in the cannon mud to generate silicon carbide, which improved the flexural strength of the cannon mud;
[0085] The compressive strength of sample Si, sample Na and sample A1 after calcination at 800℃ are 12MPa, 6MPa and 7MPa respectively; the compressive strength of the samples after calcination at 1200℃ are 26MPa, 5MPa and 6MPa respectively; with the increase of calcination temperature, the compressive strength of sample Si increases by 14MPa. Under the action of high temperature, the metallic silicon powder reacts with the carbon-based materials in the cannon mud to form silicon carbide, which improves the compressive strength of the cannon mud; after calcination at 1450℃, the compressive strength of sample Si decreases, mullite is sintered inside the sample Si, the mullite grains grow and expand, the number of cracks in sample Si increases, and its compressive strength is reduced.
[0086] ② Bulk density and apparent porosity: The bulk density of the sample Si after calcination at 800℃ is the smallest, which is 2.044g / cm 3 At this temperature, the Si sample has more volatiles, larger volume expansion, and smaller volume density. After being calcined at 1200℃, the volume density of the Si sample is the largest, reaching 2.112 g / cm 3 , the metal silicon powder and carbon-based materials sintered to form silicon carbide, resulting in volume shrinkage and a maximum volume density; after calcination at 1450°C, the volume density of the sample Si dropped to 2.105 g / cm 3 The internal sintering of sample Si generates mullite, and the mullite grains grow and expand, resulting in a slight decrease in bulk density. After sample Na and sample A1 are calcined at 1200℃, the bulk density decreases due to the volatilization of tar and asphalt. The bulk density of sample A1 is 2.065g / cm 3 The volume density of sample Na is 2.039 g / cm 3 , the main mineral phase of sodium-based bentonite, montmorillonite, has strong adsorption capacity and large expansion coefficient, and the bulk density of sample Na is lower than that of sample A1;
[0087] After calcination at 800°C, the apparent porosities of samples Si, Na and A1 were 28.8%, 28.1% and 28.6%, respectively. With the increase of heat treatment temperature, the porosity of samples Na and A1 increased slightly. After calcination at 1200°C, a large amount of components volatilized and the porosity increased. After calcination at 1450°C, the porosity decreased. Samples Na and A1 were sintered, resulting in a decrease in porosity. With the increase of heat treatment temperature, the porosity of sample Si has been decreasing. The addition of metal silicon powder can promote the sintering of cannon clay, and the amount of pores closed by sintering is greater than the amount of pores generated by the volatilization of the system. Adding metal silicon powder to cannon clay can greatly reduce the apparent porosity of the cannon clay.
[0088] ③ Line change rate: After sample Si, sample Na and sample A1 were calcined at 800℃, 1200℃ and 1450℃ (the line change is generally controlled between 0.8-1.6, greater than 1 represents sample expansion, less than 1 represents sample contraction, and the ideal state of cannon clay is slight expansion, that is to say, the line change rate does not exceed 1.6 after the calcination temperature is 1450℃), the line change rate of sample Na showed a downward trend when the heat treatment temperature increased from 800℃ to 1200℃, and the line change rate dropped to 0.7. Sample Na continued to sinter, causing the volume to shrink; overall, the cannon clay with the addition of three different micropowders expanded at 1450℃, the line change rate of Si cannon clay was 1.25, and the addition of metallic silicon powder to the cannon clay can produce slight expansion.
[0089] ④ High-temperature mechanical properties: Sample Na has the highest high-temperature flexural strength. After sodium-based bentonite is added to the cannon mud and calcined at 1400℃, there is less liquid phase and the sintering is too hard. Excessive high-temperature flexural strength will affect the opening performance of the cannon mud, consume more opening bricks, and waste costs; and after the cannon mud with the addition of metallic silicon powder and alumina powder is calcined at 1400℃, the metallic silicon powder and the carbon in the cannon mud composition form silicon carbide whiskers that produce a liquid phase at 1400℃, reducing the high-temperature flexural strength of the cannon mud; the alumina powder and the nitride in the composition form AIN whiskers that produce a liquid phase at 1400℃, the high-temperature flexural strength of the cannon mud decreases, and the opening performance of the cannon mud is improved.
[0090] ⑤ Marshall value: The Marshall value of sample A1 is too large, and the plasticity is not very good, which makes it difficult to block the iron mouth when the taphole is used; the taphole mud with added sodium-based bentonite has the smallest Marshall value, the taphole mud strength is soft, and more taphole mud is consumed under the same mud extruder pressure; the taphole mud sample with added metallic silicon powder has a medium Marshall value and the best plasticity.
[0091] ⑥XRD diffraction analysis: 6.1: XRD diffraction analysis of adding metal silicon powder to the taphole mud: After the sample Si is calcined at 1450℃, the main mineral phases are aluminum oxide, silicon nitride, silicon dioxide, silicon carbide, and 16.67% of mullite new phase is generated. The silicon carbide content in the formula is 11%, and after calcination at 1450℃, the silicon carbide content increases to 14.58%. The metal silicon powder reacts with the carbon material in the taphole mud to generate 3.58% silicon carbide in the form of whiskers, which improves the flexural strength and compressive strength of the taphole mud;
[0092] 6.2: XRD diffraction analysis of the taphole mud with sodium bentonite added: the main mineral phases of the taphole mud with sodium bentonite added are mainly silicon nitride, aluminum oxide, silicon dioxide, and silicon carbide. A new mineral phase of zeolite is generated, and 22.2% of the new phase of mullite is generated. The volume of the taphole mud expands too much, and the gap inside the taphole mud increases. When the molten iron flows through the taphole mud, it enters the gap and destroys the iron mouth; the content of silicon carbide is reduced from the initial 14% to 10.1%. The reduction in silicon carbide content leads to a decrease in the anti-erosion and anti-scouring properties of the taphole mud;
[0093] 6.3: XRD diffraction analysis of cannon clay with the addition of alumina powder: The main mineral phases of cannon clay with the addition of alumina powder are mainly alumina, silicon nitride and silicon carbide, and 2% of silicon dioxide and 13% of mullite new phases are generated, which improve the high-temperature strength of the cannon clay; 12% of quartz is generated in the cannon clay, which improves the refractoriness of the cannon clay.
[0094] ⑦Scanning electron microscope analysis: 7.1: Scanning electron microscope analysis of cannon mud with addition of metal silicon powder: Adding metal silicon powder to cannon mud generates a small amount of silicon carbide whiskers under high temperature, which has a toughening effect and improves the use strength of cannon mud under high temperature; the particles are tightly connected by sintering of metal silicon powder. It can be seen that the addition of metal silicon powder can not only improve the high-temperature use strength of cannon mud, but also fill pores, reduce apparent porosity, and make the structure denser;
[0095] 7.2: Scanning electron microscope analysis of taphole mud with sodium bentonite added: After adding sodium bentonite, many cracks are obviously found in the taphole mud. The sodium bentonite has a high expansion rate, and the grains grow in clusters. The grain growth causes the volume to expand, thereby increasing the porosity of the taphole mud and reducing the strength. When this kind of taphole mud is used, it is easy for molten iron to penetrate into the taphole mud, and the opening becomes larger and larger, destroying the iron mouth;
[0096] 7.3: Scanning electron microscope analysis of cannon clay with added alumina powder: a small amount of cracks and pores appeared in the cannon clay with added alumina powder, but mullite was generated in the pores, which increased the strength of the cannon clay. However, the high porosity would cause molten iron to penetrate into the cannon clay and destroy the taphole. A small amount of AIN whiskers existed in the cannon clay with added alumina powder, which had a toughening effect and prevented many cracks in the cannon clay.
[0097] In summary, 1) adding metal silicon powder as an additive to the taphole mud can improve the flexural strength, compressive strength and bulk density of the taphole mud and reduce the apparent porosity of the taphole mud; the metal silicon powder combines with the carbon-based materials in the taphole mud at high temperature to generate silicon carbide. After calcination at 1450℃, the flexural strength is increased to 10.45MPa, the compressive strength is increased to 13MPa, and the bulk density is increased to 2.105g / cm 3 , the apparent porosity dropped to 25.2%; 2) Sodium-based bentonite can improve the plasticity of cannon mud, but the main mineral phase of sodium-based bentonite, montmorillonite, has strong adsorption capacity and large expansion coefficient. After heat treatment, its strength is low and its porosity is high. After calcination at 1450°C, its porosity reaches 28%; 3) Alumina micropowder is added to cannon mud and a large amount of mullite is produced after calcination. With the increase of calcination temperature, the mullite grains grow, the volume expands greatly, the volume density is small, the porosity and linear change rate are high, the porosity rises to 28.2%, and the linear change rate rises to 1.4; 4) As an additive, metallic silicon powder improves the mechanical energy and volume density at room temperature and reduces the apparent porosity. Compared with sodium-based bentonite and alumina micropowder, it is more suitable to be added to cannon mud.
[0098] Effect of the amount of metallic silicon powder added on the performance of cannon mud: Metal silicon powder added as an additive to cannon mud can improve the flexural strength, compressive strength, and bulk density of cannon mud, and reduce the apparent porosity of cannon mud; the effect of the amount of metallic silicon powder added on the performance of cannon mud was analyzed, and 5%, 7%, and 9% of metallic silicon powder were added to the cannon mud respectively to find out the optimal amount of metallic silicon powder; the sample with 5% metallic silicon powder added was recorded as sample 5Si, the sample with 7% metallic silicon powder added was recorded as sample 7Si, and the sample with 9% metallic silicon powder added was recorded as sample 9Si; the specific experimental plan is shown in Table 6.
[0099] Table 6 Experimental formula / wt%
[0100]
[0101]
[0102] ① Mechanical properties at room temperature: After adding different amounts of metal silicon powder and calcining at 800℃, 1200℃ and 1450℃, after heat treatment at 800℃, the flexural strength of sample 5Si is 1.5MPa, the flexural strength of sample 7Si is 1.9MPa, and the flexural strength of sample 9Si is 1.4MPa. This is due to the volatilization of organic matter such as tar and asphalt at this temperature; after calcining at 1200℃, the flexural strength of sample 5Si, sample 7Si, and sample 9Si all increase, and the flexural strengths are 5.2MPa, 6.3MPa, and 8.6MPa, respectively; after calcining at 1450℃, sample 7Si reaches the maximum flexural strength of 10.45MPa, the flexural strength of sample 9Si is 8.5MPa, and the flexural strength of sample 5Si is 8.7MPa. The addition of 7% metal silicon powder has completely reacted with the carbon-based materials in the component, and the excess metal silicon powder acts as fine powder, reducing the flexural strength;
[0103] The taphole mud with different contents of metallic silicon powder was calcined at 800℃, 1200℃ and 1450℃. After calcination at 800℃, the compressive strength of sample 5Si was 12MPa, the compressive strength of sample 7Si was 10MPa, and the compressive strength of sample 9Si was 13MPa; when the heat treatment temperature was 1200℃, the compressive strengths of samples 5Si, 7Si and 9Si were 26MPa, 28MPa and 21MPa respectively; when the heat treatment temperature was 1450℃, the compressive strength of sample 9Si reached the maximum compressive strength of 31MPa, and the compressive strength of the samples increased with the increase of the amount of metallic silicon powder added.
[0104] ② Bulk density and apparent porosity: After calcination at 1450℃, with the increase of metal silicon powder content, the volume density of sample 7Si reached a maximum value of 2.105g / cm 3 The volume densities of sample 5Si and sample 9Si are 2.04 g / cm 3 , 2.041g / cm 3 , 7% of the metal silicon powder reacted completely with the carbon-based materials in the components, and the additional metal silicon powder did not increase the apparent porosity of the taphole mud;
[0105] After calcining at 800℃, the apparent porosity of the three cannon muds with different contents of metal silicon powder is very large, reaching more than 28%, which is caused by the volatilization of the cannon mud oil and asphalt in the cannon mud; after calcining at 1200℃, with the increase of metal silicon powder content, the apparent porosity of sample 5Si, sample 7Si and sample 9Si is 27%, 26% and 28% respectively; after calcining at 1450℃, the apparent porosity of samples 5Si, 7Si and 9Si is 27.4%, 25.2% and 27.9% respectively; 7% metal silicon powder reacts completely with the carbon-based materials in the component, promotes the sintering of cannon mud and reduces the apparent porosity; adding 7% metal silicon powder to cannon mud can increase the volume density and reduce the apparent porosity.
[0106] ③ Line change rate: After calcination at 1450℃, the line change rates of the cannon clay samples with different contents of metallic silicon powder added reached the maximum value. The line change is generally controlled between 0.8-1.6. A value greater than 1 represents sample expansion, and a value less than 1 represents sample contraction. The ideal state of cannon clay is slight expansion, and the line change rate of cannon clay increases with the increase of heat treatment temperature. Sample 7Si is sintered after calcination at 1200℃, and its volume shrinks slightly. After calcination at 1450℃, its volume expands slightly, satisfying the use effect of slight expansion of cannon clay.
[0107] ④ High-temperature mechanical properties: The high-temperature flexural strength of the taphole mud also increases accordingly. Metallic silicon powder is added to the taphole mud, and it reacts with the carbon-based materials in the taphole mud to form silicon carbide whiskers, which can improve the flexural strength of the taphole mud. The high-temperature flexural strength of the taphole mud with 5% metallic silicon powder is less than 3MPa, which is easy to damage the iron outlet when the taphole mud is opened. The high-temperature flexural strength of the taphole mud with 9% metallic silicon powder is greater than 4MPa. Excessive high-temperature flexural strength makes it difficult to open the blast furnace to tap molten iron.
[0108] ⑤ Marshall value: With the increase of metallic silicon powder content, the Marshall value of taphole clay increases slightly, and the Marshall value changes very little. The amount of metallic silicon powder added is not the main factor in the change of the Marshall value.
[0109] ⑥XRD diffraction analysis: The main mineral phases of the three samples are aluminum oxide, silicon nitride, silicon carbide, and a large amount of new mullite phase is generated. The content of silicon carbide in the Si component of sample 7 is significantly higher than that of the other two groups. The increase in silicon carbide content improves the slag and erosion resistance of the cannon mud.
[0110] ⑦Scanning electron microscope analysis: Adding 5% metallic silicon powder will produce a small number of whiskers in the cannon mud. The whiskers have different shapes, directions, sizes and are unevenly distributed. The whiskers of the cannon mud sample with 7% metallic silicon powder are very dense, the shape of the whiskers is relatively neat and linear, the distribution of the whiskers is uniform, and the whiskers are long. The whiskers can increase the toughness of the cannon mud and improve the strength of the cannon mud. The whisker content of the cannon mud sample with 9% metallic silicon powder is very small, and the whiskers are not complete, so that there are many pores inside the cannon mud. The whiskers produced by adding 7% metallic silicon powder to the cannon mud are the best.
[0111] In summary, adding 7% metallic silicon powder to the taphole mud and fully sintering it will generate a large number of silicon carbide whiskers, improve the flexural strength and bulk density of the taphole mud, reduce the apparent porosity of the taphole mud, and have a suitable linear change rate and high-temperature flexural strength; after calcination at 1450℃, the taphole mud has a flexural strength of 10.45MPa and a bulk density of 2.105g / cm 3 The apparent porosity is 25.2%, and adding 7% metallic silicon powder is the optimal addition amount for cannon mud.
[0112] A comparison of the main technical parameters of the anhydrous cannon clay prepared with additives for anhydrous cannon clay in Examples 1 to 4 (the additives account for 10wt% of the anhydrous cannon clay) and ordinary anhydrous cannon clay under the same conditions is shown in Table 7. From the comparison of the main technical parameters in Table 7, it can be seen that this specific implementation method has significant progress.
[0113] Table 7 Comparison of main parameters
[0114]
Claims
1. A method for preparing anhydrous taphole mud additive, characterized in that: First, 20-30wt% of 85 alumina clinker, 15-25wt% of forsterite, 4-6wt% of pyrophyllite, 6-8wt% of 95 silicon carbide, 5-7wt% of 90 silicon carbide, 22-27wt% of ferrosilicon nitride, 9-13wt% of coke powder, 6-8wt% of metal Si powder and 14-20wt% of white mud are used as raw materials, and then 2-4wt% of high-temperature asphalt, 1-2wt% of carbon black and 15-18wt% of cannon mud oil are added to the raw materials, and the mixture is mixed in a mixer for 20-30 minutes to obtain an anhydrous cannon mud additive.
2. The method for preparing anhydrous taphole mud additive according to claim 1, characterized in that: The particle size of the 85 alumina clinker is 10-19wt% in the range of 3-1mm, 7-13wt% in the range of 1-0mm, and 3-5wt% in the range of ≤0.074mm.
3. The method for preparing anhydrous taphole mud additive according to claim 1, characterized in that: The forsterite particle size of 3-1 mm accounts for 9-19 wt %, 1-0 mm accounts for 6-13 wt %, and ≤0.074 mm accounts for 2-5 wt %.
4. The method for preparing an anhydrous taphole mud additive according to claim 1 or 3, characterized in that: The forsterite can be replaced by 11-24wt% of fused magnesia, wherein the particle size of the fused magnesia is 9-19wt% for 3-1mm, 6-13wt% for 1-0mm, and 2-5wt% for ≤0.074mm.
5. The method for preparing an anhydrous taphole mud additive according to claim 1 or 3, characterized in that: The forsterite can be replaced by 10-20wt% of quartz sand, wherein the quartz sand with a particle size of 3-1mm accounts for 9-19wt%, the quartz sand with a particle size of 1-0mm accounts for 6-13wt%, and the quartz sand with a particle size of ≤0.074mm accounts for 2-5wt%.
6. The method for preparing an anhydrous taphole mud additive according to claim 1, characterized in that: The metal Si powder can be replaced by 5-7 wt% of aluminum oxide powder.
7. The method for preparing anhydrous taphole mud additive according to claim 1, characterized in that: The metal Si powder can be replaced by 7-8 wt % of sodium bentonite.
8. The method for preparing an anhydrous taphole mud additive according to claim 1, characterized in that: The metal Si powder can be replaced by 5-8wt% silicon-carbon micropowder with a particle size of 3000 mesh.
9. The method for preparing an anhydrous taphole mud additive according to claim 1, characterized in that: The particle size of the pyrophyllite is 3-1mm; the particle size of the 95 silicon carbide is 1-0mm; the particle size of the coke powder is 1-0mm90; the particle size of the silicon carbide is ≤0.074mm; and the particle size of the ferrosilicon nitride is ≤0.074mm.
10. An additive for anhydrous taphole mud, characterized in that: The anhydrous cannon clay additive is an anhydrous cannon clay additive prepared by the preparation method of the anhydrous cannon clay additive according to any one of claims 1 to 9.
Citation Information
Cited By
Preparation method of metal toughened silicon carbide-silicon nitride stemming material
CN120329013A